Media Development of Animated Learning Videos Pure Substance and Mixture Substance in 5th Grade Elementary School - Bunga Ayu Dibtasari; Esti Untari; Sutansi Sutansi (Unversitas Muhammadiyah Mataram, 2022)
Abstract: The purpose of this study was to produce an animated video media of learning pure substances and mixture substances of class V at SDN Pesantren 2 Kota Kediri. The model used in this study is a 4D Thiagarajan model consisting of four stages of research, namely define, design, development, and dissemination. Material expert validation results obtained a percentage of 100%, media experts obtained a percentage of 95.83%, users (teachers) obtained a percentage of 93.75%. Meanwhile, the results of product attractiveness trials in grade V students of SDN Pesantren 2 Kota Kediri, namely small-scale trials of 97.05%, and large-scale trials of 93.88%. It can be concluded that the learning animation video media has been interesting and worthy to be used as a learning medium in the process of teaching and learning activities.Abstrak: Tujuan dari penelitian ini, yaitu menghasilkan media video animasi pembelajaran zat tunggal dan zat campuran kelas V di SDN Pesantren 2 Kota Kediri. Model yang digunakan dalam penelitian ini adalah model 4D Thiagarajan yang terdiri dari empat tahapan penelitian, yaitu pendefinisian, perancangan, pengembangan, dan diseminasi. Hasil validasi ahli materi diperoleh persentase 100%, ahli media diperoleh persentase 95,83%, pengguna (guru) diperoleh persentase 93,75%. Sedangkan hasil uji coba kemenarikan produk pada siswa kelas V SDN Pesantren 2 Kota Kediri, yaitu uji coba skala kecil 97,05%, dan uji coba skala besar 93,88%. Dapat disimpulkan media video animasi pembelajaran sudah menarik dan layak digunakan sebagai media pembelajaran dalam proses kegiatan belajar mengajar.